The Analysis of Inflation Determinants in Indonesia - T. Citra Nisa Farza (Proceedings of AICS - Social Sciences, 2017)
This study aims to analyze the effects of money supply, BI Rate, and exchange rate to inflation in Indonesia. The type of data in this study is secondary data in the form of time series obtained from the Badan Pusat Statistik and Bank Indonesia. The analysis was done by co-integration equation with Error Correction Model (ECM) method. This study analyzes the relationship between independent and dependent variables in both the short and long term. The estimation results showed that in the short-term, the variable of BI Rate and exchange rate has significant effect to inflation in Indonesia. ECM model is considered valid because the value of Error Correction Term (ECT) is significant and negative of -1.318219. The results also showed that in the long-term only the variable of BI Rate which has significant effect to inflation in Indonesia